Acute effect of a judo contest on muscular performance parameters and physiological response - Serrano-Huete, V.; Latorre-Roman, P. A.; Garcia-Pinillos, F.; Morcillo Losa, J. A.; Moreno-Del Castillo, R.; Parraga-Montilla, J. A. (International Journal of Kinesiology & Sports Science, 2016)
It is necessary to know accurately the physical effects of judo contest on athletes in order to quantify how successive judo bouts impair muscular performance parameters and physiological response associated with the aim to create specific training programs that take the demands of judo bout into account. Purpose: The purpose of current study was to characterise the evolution of muscular performance parameters and physiological response during a judo contest. Methods: Twenty-nine men performed five 5-minute bouts with 15 minutes of passive rest. Immediately after the bouts, some muscular performance parameters and physiological variables were measured, in this order: Borg´s rate of perceived exertion (RPE), maximal dynamic strength in upper body (MDS), countermovement jump (CMJ), dominant (DHS) and non-dominant handgrip isometric strength (NDHS). Lactate (LAC) was measured 3 minutes after each bout and 1 minute before the next too). Heart rate (HR) was monitored during the contest. ANOVA to compare baseline test data and successive bouts was used. Results: ANOVA revealed significant differences in HRmean (p=0.045), LAC (p<0.001) and in RPE (p<0.001). A decrease in NDHS (p<0.001), DHS (p<0.001), MDS (p<0.001) was found. Some significant correlations were found between NDHS and DMPV (r=0.368, p=0.050), DMS (r=0.369, p=0.050) and DMXS (r=0.405, p=0.029); between DHS and DLACb (r=0.430, p=0.020), DMXS (r=0.379, p=0.043), DMP (r=0.369, p=0.050) and DRPE (r=0.456, p=0.013); between CMJ and DPM (r=0.381, p=0.041), DPMX (r=0.417, p=0.024), DFM (r=0.423, p=0.022) and DDHS (r=0.348, p=0.040). These results show a high decrease of muscular performance parameters and an increase of physiological parameters, specially between baseline test and postbout 5, but gradual between all bouts. Conclusion: Judo contest can be considered a high intensity exercise, due to high levels of physiological parameters and the decrease in force production obtained.